33 THE IMPACT OF PRE-TRANSPLANT FLOW CYTOMETRY CROSSMATCHES ON RENAL ALLOGRAFT OUTCOME: A PILOT STUDY. (1st January 2005) - O'Brien, R.; Yao, L.; Arora, B.; Frey, D.; Boudreaux, P.; Daley, I.; Thiagarajan, R.; Kumar, P.
Abstract : Background: Pre-transplant complement dependent cytotoxicity (CDC) crossmatch is an established procedure known to influence renal allograft survival rates. The relatively new flow cytometry crossmatch (FCXM) is considered more sensitive, and based on literature reports, is believed to enhance renal allograft outcome. Before utilizing this procedure, some programs are requiring center specific data. Purpose: The purpose of this study was to investigate the impact of a positive flow crossmatch on renal allograft outcome in a single center. Method: A total of 56 patients who received renal transplants at the Transplant Institute of New Orleans were investigated. The pre-transplant workup included a crossmatch to be performed by both a complement dependent cytotoxicity (CDC) assay as well as by flow cytometry. A negative CDC crossmatch against donor T cells was required for inclusion in the study. The results of the flow crossmatch were not used for excluding patients for getting a transplant. The clinical outcome in terms of successful versus failed transplants was recorded over a three year period. A failed graft was defined as return to dialysis. Result: Nine out of fifty-six renal allografts failed due to immunologic rejections. An additional two grafts were lost due to other reasons. Amongst those who lost the renal grafts due to rejection, thirty-three percent had a positive pre-transplant flow crossmatch. On the other hand, the flow crossmatch was positive in sixteen percent of those who had functioning renal grafts. Conclusion: Although these numbers are small, the data suggest that positive flow cytometry crossmatches are related to lower renal allograft survival rates at our center. Further studies will be performed on a larger patient population.